Encouraging a Critical Consciousness in the Spanish as Foreign Language classroom: Action Research - Bori, Pau (Didáctica. Lengua y Literatura, 2022)
Drawing on the principles of critical pedagogy, this article presents an action research study in a Spanish as a foreign language (SFL) classroom at the University of Belgrade that aims to challenge the dominant instrumental trend in foreign language education in the era of neoliberalism. To do this, an anti-hegemonic and dissenting didactic proposal is developed to turn the SFL classroom into a space for dialogue and reflection on our social reality and thus help students to become critical citizens. The results of the implementation of the didactic proposal in the classroom show that its benefits go beyond the linguistic aspects towards the development of a critical consciousness among the students.